Nurses' perception about the quality of care provided to patients in a situation of hospitalization in the emergency rooms (Research, Society and Development, 2022)
Aim: To analyze the nurses’ perception about the quality of nursing care provided to patients in a situation of hospitalization in the Emergency Room. Method: This is a descriptive and cross-sectional study carried out with the application of a structured questionnaire, via online, with Brazilian nurses who have been working in urgent and emergency services, public or private, for at least six months. The questionnaire, developed by the researchers, contains 13 questions aimed at evaluating the Urgency and Emergency Service and evaluating the nursing care offered to patients in a situation of hospitalization in the Emergency Room. Responses were rated on a seven-point Likert scale: Never, Very Rarely, Rarely, Occasionally, Often, Very Often, Always. Results: 146 nurses participated in the survey. Most evaluated overcrowding as a frequent experience, reported delays and/or difficulties in adjusting patients to a regular hospital bed, showed flaws in the nursing dimensioning for the surplus of patients and that at times of high volume of admissions, the nursing care is compromised. Conclusion: In the nurses' perception, the quality of nursing care provided to patients admitted to the emergency room is impaired when compared to care received in a regular hospital bed.